SCIENTIFIC AND TECHNICAL AND ECONOMIC APPROACH AND SOME THEORETICAL AND EXPERIMENTAL DEVELOPMENTS IN THE USE OF INDUSTRIAL WASTES IN CONSTRUCTION - Bolshakov, V. I.; Savin, L. S.; Prykhodko, O. P.; Pshinko, O. M.; Savin, Yu. L.; Dubov, T. M.; Savin, Ye. Yu. (Science and Transport Progress, 2009)
A new techno-economic approach to the use of technogenic wastes in construction is proposed in this article. The theoretical-and-experimental developments on steel corrosion kinetics in the sodium-calcium silicates with the replacement of oxygen anion on fluorine and chlorine are given. In this study some physico-chemical principles of making a new glass subclass with chlorine-containing anionic complexes are presented.